85.5k views
2 votes
Which expression is equivalent to (x^6y^8)^3\x^2y^2

2 Answers

6 votes

Answer:


\large\boxed{((x^6y^8)^3)/(x^2y^2)=x^(16)y^(22)}

Explanation:


((x^6y^8)^3)/(x^2y^2)\qquad\text{use}\ (ab)^n=a^nb^n\ \text{and}\ (a^n)^m=a^(nm)\\\\=((x^6)^3(y^8)^3)/(x^2y^2)=(x^((6)(3))y^((8)(3)))/(x^2y^2)=(x^(18)y^(24))/(x^2y^2)\qquad\text{use}\ (a^m)/(a^n)=a^(m-n)\\\\=x^(18-2)y^(24-2)=x^(16)y^(22)

User Damone
by
5.3k points
3 votes

Answer:
x^(16)\ y^(22)

Explanation:

The given expression :
((x^6y^8)^3)/(x^2y^2)

Using identity ,
(a^m)^n=a^(mn) , we have


{(x^6y^8)^3=x^(6*3)\ y^(8*3)\\\\=x^(18)\ y^(24)

Now,
((x^6y^8)^3)/(x^2y^2)=(x^(18)\ y^(24))/(x^2\ y^2)

( its also an equivalent expression to given expression.)

Using identity ,
(a^n)/(a^m)=a^(n-m) , we have


(x^(18)\ y^(24))/(x^2\ y^2)=x^(18-2)\ y^(24-2)\\\\=x^(16)\ y^(22)

Hence, the expression is equivalent to given expression :


x^(16)\ y^(22)

User Ruben Marrero
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.